New Coccinellidae (Coleoptera, Coccinelloidea) from Napo Province in Ecuador - Szawaryn, Karol; Czerwiński, Tomasz (European Journal of Taxonomy, 2022)
Examination of Coccinellidae material recently collected from Napo Province in Ecuador revealed 38 species of ladybird beetles, of which six are new: Chnoodes yanayacu sp. nov., Cyrea mcclarini sp. nov., Eupalea borowieci sp. nov., Exoplectra misahualli sp. nov., Hyperaspis rutai sp. nov., Toxotoma gonzalezi sp. nov. Seven species are recorded for the first time from Ecuador: Cyrea noticollis (Mulsant, 1850), Eupalea formosa Mulsant, 1850, Epilachna transverselineata (Mader, 1858), Psyllobora marshalli Crotch, 1874, Toxotoma fuscopilosa (Weise, 1902), Toxotoma taeniola (Gordon, 1975), Zenoria linteolata Mulsant, 1850. For three species: Epilachna obtusiforma Gordon, 1975, Hinda ecuadorica Gordon & Canepari, 2013 and Siola atra González, 2015, supplementary notes on the original descriptions are provided. New name combinations are proposed for six species, which are transferred to the genus Toxotoma Weise, 1900: Toxotoma aequatorialis (Gordon, 1975), Toxotoma chigata (Gordon, 1975), Toxotoma flavocirculus (González, 2015), Toxotoma fuscopilosa, Toxotoma hybridula (Gordon, 1975), Toxotoma taeniola. The occurrence of Scymnus interruptus (Goeze, 1777) in Ecuador is also confirmed.